First principles of meteorology and air pollution - Lazaridis, Mihalis (Environmental Pollution, 2011)
This books main objective is to decipher for the reader the main processes in the atmosphere and the quantification of air pollution effects on humans and the environment, through first principles of meteorology and modelling/measurement approaches. The understanding of the complex sequence of events, starting from the emission of air pollutants into the atmosphere to the human health effects as the final event, is necessary for the prognosis of potential risk to humans from specific chemical compounds and mixtures of them. The book focuses on such topics as: Integrated study of air pollution, from sources to effects. Comprehensive study of meteorology and air pollution and their interactions. State-of-the-science study of atmospheric chemistry and physics. Indoor air pollution in conjunction with human exposure. Air pollution legislation and human health This book fills a gap in the literature by providing a solid grounding in the first principles of meteorology and air pollution, making it particularly useful for undergraduate students. Its broad scope makes it a valuable text in many related disciplines, containing a comprehensive and integrated methodology to study the first principles of air pollution, meteorology, indoor air pollution, and human exposure. Problem-solving exercises at the end of each chapter make this especially worthwhile as a classroom text.